Nonlinear dynamic analysis of gear system in shearer cutting section under wear failure. (March 2022) - Sheng, Lianchao; Li, Wei; Ye, Guo; Feng, Ke
Gear wear failure is one of the important failures of the gear system in the shearer cutting section. To reveal the influence mechanism of shearer cutting gear wear on the system dynamic characteristics, considering coupling factors such as time-varying meshing stiffness, dynamic gear clearance, internal error excitation, end load constraint and bearing radial clearance under wear failure, an improved dynamic model of shearer drive gear system is introduced to present an in-depth investigation of uniform wear of gear teeth effect. The dynamic meshing stiffness of gears under different degrees of wear is analysed. Furthermore, the bifurcation diagram is utilized to observe the motion state of the system experiencing different excitation frequencies, support damping as well as terminal loads. It is demonstrated that the gear surface wear could bring a change in gear dynamic transmission error, vibration impact state and amplitude, which is mainly manifested in increasing the unstable area and the vibration amplitude of the gear system, providing a method for monitoring and diagnosing of gear surface faults.